(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The right to a clean environment is essential and closely connected to the proper to health and well-being. It’s of fundamental importance to note there is a sturdy connection between the quality of the environment and so the health of the people living andor exposed to the environment. Quality life is possible only in a very excellent environment with clean air to breathe, safe water to drink and noiseless atmosphere. Environmental pollution is one altogether the foremost severe problems that the present living beings face today. Many people do not have access to clean air and water and knowledge health problems due to the ever increasing pollution. One in all the foremost dangerous Pollution which don’t effect living creatures directly but also indirectly. The cause is that the buildup of solid and liquid waste materials that contaminate groundwater and soil. These waste materials are often remarked as municipal solid waste (MSW), which includes both hazardous and non-hazardous waste. When waste is deposited onto a component of land, the permeability of the soil formations below the waste can increase or reduce the prospect of land pollution. Before that, waste was typically left on top of the underside in “open dumps,” which resulted in rats, mosquitoes, and other disease infestations, further as foul smells and windblown debris. This article is specially written to evaluation the impacts of such land pollution and the way the effect might be decreased with some measures.